Analisis Representasi Lesbian, Gay, Biseksual, dan Transgender (LGBT) pada Lima Game Online - Ayu Puspita Sari, Dyah (Icon: Islamic Communication and Contemporary Media Studies, 2025)
In an online game, there is a representation in the visual aspect, narrative, dialogue, and character interaction that shows Lesbian, Gay, Bisexual, and Transgender (LGBT) behavior. This is very unacceptable in the view of Islam because basically humans have been created in pairs between men and women, not with the same sex. The purpose of this study is to determine the representation of Lesbian, Gay, Bisexual, and Transgender (LGBT) in five online games and to determine Islam's view on LGBT representation in online games. The data analysis used John Fiske's semiotic model. The results of the study on five online games containing LGBT elements found a level of reality through appearance codes, movement codes, environmental codes, speech style codes, and expression codes. In addition, there is also a level of representation through narrative code, character code, action code, dialogue code, and background code. Finally, the level of ideology is found which is produced from reality and representation which contains the ideology of liberalism, the ideology of humanism, and the ideology of individualism.